A Translation Analysis of Techniques used in the War Speech Event at the Novel “Ghost Fleet ; a Novel of the New World War”, Written by P.W. Singer and August Cole from English into Indonesian - Adib Darmawan (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2022)
Translating literary works, especially novels, causes multiple challenges for translators, including the implementation of techniques in translating utterances in accordance with their contexts. This study was especially intended to identify and analyse the techniques used in the translated novel from English into Bahasa Indonesia. It is a translation research: a case study with descriptive qualitative method on the basis of the documents of the ST and TT. The case study was applied to a novel Ghost Fleet: A Novel of  The Next World. The data were obtained using document analysis and Focus Group Discussion (FGD). The data were analyzed one by one using Spradley‟s four procedures.The results showed  tha hhe utterances were translated using established equivalence. variation, pure borrowing, explicitation, modulation, implicitation, particularization, compensation, discursive creation, reduction, literal translation, trans-rank-shift, transposition, addition and generalization. This research revealed that in the war speech event, the techniques used.